CTLA4 as Immunological Checkpoint in the Development of Multiple Sclerosis. Issue 2 (15th July 2016) - Gerdes, Lisa Ann; Held, Kathrin; Beltrán, Eduardo; Berking, Carola; Prinz, Jörg C.; Junker, Andreas; Tietze, Julia K.; Ertl‐Wagner, Birgit; Straube, Andreas; Kümpfel, Tania; Dornmair, Klaus; Hohlfeld, Reinhard
Abstract : We investigated a patient who developed multiple sclerosis (MS) during treatment with the CTLA4‐blocking antibody ipilimumab for metastatic melanoma. Initially he showed subclinical magnetic resonance imaging (MRI) changes (radiologically isolated syndrome). Two courses of ipilimumab were each followed by a clinical episode of MS, 1 of which was accompanied by a massive increase of MRI activity. Brain biopsy confirmed active, T‐cell type MS. Quantitative next generation sequencing of T‐cell receptor genes revealed distinct oligoclonal CD4 + and CD8 + T‐cell repertoires in the primary melanoma and cerebrospinal fluid. Our results pinpoint the coinhibitory molecule CTLA4 as an immunological checkpoint and therapeutic target in MS. Ann Neurol 2016;80:294–300